Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1111/j.1471-0528.1992.tb13791.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membrane composition in pregnancy‐induced hypertension: evidence for an altered lipid profile

Abstract: Objective To investigate whether the increased membrane fluidity postulated as a possible contributing factor to the hypertensive states of pregnancy is related to the lipid composition of the erythrocyte membrane. Design An observational case control study. Subjects 30 women with pregnancy induced hypertension, 26 normotensive pregnant women matched for gestational age, and 10 normotensive non pregnant nulliparous women. Interventions Erythrocyte membranes were prepared from venous blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In the case of the group of pregnant women with PIH a statistically significant (p < 0.05) increase of total cholesterol concentration was found in comparison with the control group. This is consistent with the data published by Anceschi et al (1992), among others, who found a total cholesterol concentration increase and an increase of cholesterol/phospholipid ratio in the women with pregnancy-induced hypertension. Van den Elzen et al (1996) found a close relation between gestosis development and a total cholesterol level increase and HDL-cholesterol increase.…”
Section: Resultssupporting
confidence: 95%
“…In the case of the group of pregnant women with PIH a statistically significant (p < 0.05) increase of total cholesterol concentration was found in comparison with the control group. This is consistent with the data published by Anceschi et al (1992), among others, who found a total cholesterol concentration increase and an increase of cholesterol/phospholipid ratio in the women with pregnancy-induced hypertension. Van den Elzen et al (1996) found a close relation between gestosis development and a total cholesterol level increase and HDL-cholesterol increase.…”
Section: Resultssupporting
confidence: 95%
“…23 Increased cholesterol/ phospholipid ratio of the erythrocyte membrane in women with pregnancy induced hypertension has been observed in studies. 24 The association of abnormal lipid values in the promotion of hypertension in pregnant women helps to investigate the underlying pathological process of hypertension in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Erythrocyte aggregability increases in myocardial infarction, angina, inflammation, diabetes, hypertension, and stroke; adherence to endothelial cells increases in inflammation diabetes and stroke; deformability decreases in infarction, angina, inflammation, diabetes, hypertension, and stroke (26). Cholesterol erythrocyte membrane is a dynamic component of the erythrocyte membrane lipids that is subject to modifications associated with a variety of physiological, pathological, and pharmacologic conditions: it has been reported to increase with age (27), chronic alcohol assumption (28), obesity in women (29), pregnancyinduced hypertension (30), and after cyclosporine A administration (31). Cholesterol erythrocyte membrane decreases after exercise (32), in nephrotic syndrome (33), rheumatoid arthritis (34), and cerebral hemorrhage (35).…”
Section: See Page 2081mentioning
confidence: 99%